2021
DOI: 10.21203/rs.3.rs-231909/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Diabetes in Patients Waiting for Invasive Cardiac Procedures During COVID-19 Pandemic

Abstract: Background: During COVID-19 pandemic, elective invasive cardiac procedures (ICP) have been frequently cancelled or postponed. Consequences may be more evident in patients with diabetes. Objectives: The objective was to identify the peculiarities of patients with DM among those in whom ICP were cancelled or postponed due to the COVID-19 pandemic, as well as to identify subgroups in which the influence of DM has higher impact on the clinical outcome.Methods: We included 2,158 patients in whom an elective ICP was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In previous studies, we showed that, during the first weeks of the lockdown in March and April 2020, some interventional procedures fell markedly, such as primary angioplasty 6 and TAVI. 12 However, this article is the first to compile the totality of procedures in Spain throughout 2020. Notably, the observed reduction was lower than that described during the first weeks of the first lockdown, which indicates a rebound in activity after the first wave of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we showed that, during the first weeks of the lockdown in March and April 2020, some interventional procedures fell markedly, such as primary angioplasty 6 and TAVI. 12 However, this article is the first to compile the totality of procedures in Spain throughout 2020. Notably, the observed reduction was lower than that described during the first weeks of the first lockdown, which indicates a rebound in activity after the first wave of the pandemic.…”
Section: Discussionmentioning
confidence: 99%